2015
DOI: 10.1002/pssa.201431942
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cu2ZnSnS4solar cell fabricated by sulfurization of metallic precursor Mo/Zn/Cu/Sn

Abstract: Various characterization methods are implemented to investigate the fundamental properties of a Cu2ZnSnS4 (CZTS) solar cell. The chemical distribution across the CZTS grain boundaries, the surface potential of CZTS absorber, the minority lifetime, the carrier collection length, diode ideality factor, dark saturation current, and series resistance are revealed in the characterization measurement. The short minority lifetime, high defect density, and large series resistance are confirmed and need to be addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The net carrier density in CZTS bulk was derived from C-V scans with different frequencies as shown in Figure 2a. Several papers have reported that in polycrystalline materials, the presence of deep level defects can well enhance the capacitance response at inappropriate low frequencies resulting in misleading interpretation of net carrier density [20][21][22]. When AC angular frequency is slow enough, deep level defects could have sufficient time to respond, thereby adding enormous amount of extra charge to thin film [20].…”
Section: C-vmentioning
confidence: 99%
“…The net carrier density in CZTS bulk was derived from C-V scans with different frequencies as shown in Figure 2a. Several papers have reported that in polycrystalline materials, the presence of deep level defects can well enhance the capacitance response at inappropriate low frequencies resulting in misleading interpretation of net carrier density [20][21][22]. When AC angular frequency is slow enough, deep level defects could have sufficient time to respond, thereby adding enormous amount of extra charge to thin film [20].…”
Section: C-vmentioning
confidence: 99%
“…Kesterite thin films have been prepared using various vacuum-based techniques including sputtering [42][43][44][45], thermal evaporation [46][47][48], pulsed laser deposition [49,50].…”
Section: Vacuum Approachesmentioning
confidence: 99%